2008
DOI: 10.1159/000163045
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hormone Replacement Therapy on Insulin Resistance and Platelet Function Tests

Abstract: Objectives: The aim of this study was to evaluate measures of insulin resistance and platelet function in postmenopausal women with oral or transdermal hormone replacement therapy (HRT). Subjects and Methods: Eighty women divided into four groups of 20 each were enrolled in the study. Group 1: postmenopausal hysterectomized women who received only transdermal estradiol (13.9 mg/12.5 cm2); group 2: women with intact uterus who were treated with estrogen-progestin combination (HRT); group 3: postmenop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Overall, in vitro and animal studies strongly suggest that E2 has a protective effect in females by enhancing fatty acid oxidation and reducing hepatic lipogenesis. In humans, several studies demonstrated that E2 therapy improves insulin sensitivity and glucose homeostasis in postmenopausal women [55][56][57]. However, limited studies have shown a beneficial effect of hormone replacement therapy on NAFLD [58].…”
Section: Estrogensmentioning
confidence: 99%
“…Overall, in vitro and animal studies strongly suggest that E2 has a protective effect in females by enhancing fatty acid oxidation and reducing hepatic lipogenesis. In humans, several studies demonstrated that E2 therapy improves insulin sensitivity and glucose homeostasis in postmenopausal women [55][56][57]. However, limited studies have shown a beneficial effect of hormone replacement therapy on NAFLD [58].…”
Section: Estrogensmentioning
confidence: 99%